Late glacial to Holocene sea-level changes in the Sea of Marmara: new evidence from high-resolution seismics and core studies - Eriş, Kürşad Kadir; Cagatay, M. N.; Akcer, Sena; Gasperini, Luca; Mart, Yosi (Geo-Marine Letters, 2011)
The late glacial to Holocene sedimentary record of the northern shelf of the Sea of Marmara (SoM) has been documented by detailed seismo-, chrono-, and biostratigraphic analyses using sub-bottom (Chirp) profiles and sediment cores. During MIS 3 and the main part of MIS 2 (60-15 (14)C ka b.p.), disconnection from the Mediterranean and Black seas together with a dry climate resulted in a regression in the SoM, when the Sea was transformed into a brackish lake. The river incisions below 105 m water depth along the northern shelf took place during the last glacial maximum, when the lake level was modulated by stillstands at -98 and -93 m. The post-glacial freshwater transgressive stage of the Marmara 'Lake' occurred between 15 and 13.5 (14)C ka b.p., leading to a rise in water level to -85 m by 13.0 (14)C ka b.p., as evidenced by broad wave-cut terraces along the northern shelf. Since 12 (14)C ka b.p., high-frequency sea-level fluctuations have been identified at the SoM entrance to the Strait of A degrees stanbul (SoI). Thus, wave-cut terraces have been recorded at water depths of -76 and -71 m that, according to an age model for core MD04-2750, have ages of 11.5 and 10.5 (14)C ka b.p., respectively. Ancient shoreline at -65 m along the northern shelf presumably formed soon after the Younger Dryas (YD) at ca. 10.1 (14)C ka b.p. Moreover, there is compelling evidence of Holocene outflow from the Sea of Marmara to the Black Sea. At the SoM entrance to the SoI, the existence of bioherms on the reflector surface together with abundant Brizalina spathulata and Protoglobulimina pupoides in a core suggests a return to higher salinities due to strong Mediterranean water incursion into the SoM at similar to 8.8 (14)C ka b.p. This finding is consistent with earlier suggestions that, after the YD, the Black Sea was flooded by outflow from the SoM as a result of global sea-level rise.
id: 2113; PT: J; TC: 0; J9: GEO-MAR LETT; UT: WOS:000286334700001